Diversity of insect and mite species in chili ecosystem: relationship of the major pests with predator and plant damage - Nasrin, Mahbuba; Amin, Md Ruhul; Miah, Md Ramiz Uddin; Akanda, Abdul Mannan; Miah, Md Giashuddin (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The study was carried out with Capsicum frutescens variety BARI Morich 2 to explore the abundance and diversity of insect and mite species harbored in chili ecosystem. The study also determined the relationship of the abundance of major insect and mite pests with predator and chili plant damage index. The chili plants were cultivated in the experimental field of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh and the data of the insect and mite populations were collected at weekly intervals from November 2017 to June 2018. In total 41 insects and one mite species were found in the chili ecosystem where 12 species depicted as pest (three major pests and nine minor pests), 12 species as predator, four species as pollinator and 14 species were found as casual visitor. Insects of the order Hemiptera showed the highest abundance and the ant depicted the top rank with 6.7% abundance of the harbored species. The pest and pollinator species occupied the highest and lowest ranks with 35.4% and 9.3% abundances, respectively. Predator insects revealed the highest diversity and the pollinator category was the most dominant group which has the highest evenness index. The insects of the casual visitor category showed the highest richness index. The population of whitefly was positively correlated with mite, and the abundances of thrips and mite showed significant positive correlation with plant damage index. The abundance of whitefly also showed significant positive correlation with the abundance of dragon fly but negatively associated with the abundance of pirate bug. The abundance of mite had significant negative correlation with the abundance of pirate bug and hover fly, but positively correlated with lady bird beetle. The results indicated that a diversified insect group prevailed in the chili ecosystem, and they had direct linkage with existing predators and plant damage.